La enseñanza de los derechos humanos como materia de derecho internacional en tiempos de expansión, diversificación y confrontación - Almqvist, Jessica (2022)
This study analyzes some of the factors that facilitate and complicate advanced legal teaching in human rights as a subject of international law. The main objective is to offer a reflection on the challenges faced by the teacher in this field and hich arise as a result of the expansion, diversification, and confrontation of the subject taught. According to the argument developed, a classical or traditional approach to teaching inspired by international legal positivism does not offer the necessary resources to address these challenges. In its place, the study advances a wider approach that incorporates all the teaching objectives included in the common vision of Human Rights Education (HRE) and adapts them to the realm of advanced legal studies. Unlike a classical approach, the HRE-based framework fosters a more complex account of teaching tasks, which is not limited to cognitive development but extends to moral and ethical development alongside the development of action-oriented capacities. For this reason, it enables the elaboration of responses to the challenges faced that recognize the relevance of all the values sustained by international human rights law (IHRL) as guiding principles for teachers in this field. In addition, it permits a positive appreciation of the contributions made by other disciplines and critical studies of human rights, without discarding the utility of legal positivism to distinguish between IHRL as it is, from what it should be, and from what it can be.